Зарабатываем на шести сотках: это просто! / А. В. Маркин - Маркин Алексей Владимирович (Есть идея, 2006)
Экземпляры: Ф4 (20221202) / Инвентарный номер: 196895 / Цена: 30.00 / Сис.шифр: 42.34 / Авт.знак: М27 / ГРНТИ: 68.35 / ББК: 42.34